Impact of bank-specific variables on profitability: An empirical study on the banking sector of Bangladesh - Qamarullah Bin Tariq Islam (Atlantic Review of Economics (ARoEc), 2021)
– This paper analyses the impact of some bank-specific variables on the profitability of the banking sector in Bangladesh. Taking annual data for 1997 to 2019, this study analyses the impact of capitalization, non-performing loans, and cost on profitability. In this time- series analysis, augmented Dickey-Fuller tests of stationarity and Johansen cointegration tests are conducted first and then the appropriate methodology of vector error correction model is applied to examine the relationship. For the capitalization variable, where both types of relationships are possible, it is observed that it affected profitability negatively. According to expectation, it is found that cost negatively affects the profitability and is significant. For non-performing loans, a negative but insignificant relationship is found. Finally, some diagnostic tests are carried out to verify the robustness of the model. The policy implication of this paper is that banks should reduce its expense and continue to monitor non-performing loans. Moreover, banks should be careful about the capital- assets ratio above a certain threshold level.
Keywords: C32; E58; G21; 330; Bank profitability; bank-specific variables; time-series study; Bangladesh